Liver tissue changes during and post 6-month spaceflight as measured by ultrasound radio frequency signal processing - Arbeille, Philippe; Zuj, Kathryn; Guillon, Laurent (Frontiers in Physiology, 2024)
Background: Analysis of ultrasound radio frequency (RF) allows for the determination of the index of reflectivity (IR) which is a new measure that is dependent on tissue properties. Previous work has shown differences in the IR of the carotid artery wall with long duration spaceflight (Arbeille et al 2021); therefore, it was hypothesized that liver tissue would also show differences in this measure with spaceflight.Methods: The RF signal of a liver tissue sample was displayed and processed along 6 different lines covering a surface of approximately 2 x 2cm of the sample. The IR was calculated as the energy backscattered by the liver sample, divided by the total energy returned to the ultrasound probe.Results: Seven astronauts were investigated preflight, inflight on day 150, and postflight 4 days and 6 months after rerunning to Earth. Compared to preflight (65% ± 18%), the liver tissue sample IR was significantly lower on flight day 150 (49% ± 15%; p=0.022) and four days postflight (46% ± 19%; p=0.023). At 6 months postflight, the IR had returned to preflight values (59% ± 13%; p=0.941).The significant decrease of the coefficient of reflectivity means that inflight and four days postflight, the liver tissue reflected less ultrasound waves than preflight. This suggests a change in tissue properties through either the addition of particles that do not reflect ultrasound waves, or structural or cellular changes that alter the reflectivity of the tissue.